Between Jihad and Salaam: Profiles in Islam by Joyce M Davis. (New York: St. Martin's Press, Inc., 1999. 339 pages.) (American Journal of Islam and Society, 2002)
Today, politicians and political activists of every stripe recognize the powerof the international media. From the most gilded generalissimo to the grulrbiest guerrilla, there are few who would pass up a chance to plead their caseon the world stage. This has given foreign correspondents, particularlythose from first world countries like the United States, easy access tomovers and shakers across the globe. Unfortunately, understanding doesnot always come with access.Nowhere has this lack of understanding been more pervasive- or morepernicious - than among those reporters covering the Islamic world. JoyceM. Davis, deputy foreign editor for Knight Ridder newspapers and formerdeputy senior editor at National Public Radio, sets out to remedy this prolrlem in her book, Between Jihad and Salaam: Profiles in Islam. Throughinterviews with 17 "Islamic leaders," Davis endeavors "to help us understandthe intellectual vitality that is now igniting the Muslim world."However, like too many of her colleagues, the author quickly becomes lostin the surface realities of that world. In the end, her book does little to challengethe stereotypes and misconceptions she promises to shatter.Davis begins the book with an introduction that outlines her missionwhile revealing the limits of her own understanding. While she deftly dispelssome of the more blatant misunderstandings about Islam, she alsothrows around technical terms like "lslamists" and "scholars" without ...